2013
DOI: 10.1093/nar/gkt1226
|View full text |Cite
|
Sign up to set email alerts
|

The SEED and the Rapid Annotation of microbial genomes using Subsystems Technology (RAST)

Abstract: In 2004, the SEED (http://pubseed.theseed.org/) was created to provide consistent and accurate genome annotations across thousands of genomes and as a platform for discovering and developing de novo annotations. The SEED is a constantly updated integration of genomic data with a genome database, web front end, API and server scripts. It is used by many scientists for predicting gene functions and discovering new pathways. In addition to being a powerful database for bioinformatics research, the SEED also house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
2,991
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 3,882 publications
(3,112 citation statements)
references
References 32 publications
9
2,991
0
13
Order By: Relevance
“…We used the CLC genomic workbench version 7.5 (CLC Bio, Aarhus, Denmark) for de novo assembly with a 500-bp minimum threshold resulting in 127 contigs. The draft genome consisted of 4,372,178 nucleotides and was annotated by rapid annotations using subsystems technology (RAST) (12). RAST annotation showed that Acinetobacter calcoaceticus PHEA-2 (score, 503) and Acinetobacter sp.…”
mentioning
confidence: 99%
“…We used the CLC genomic workbench version 7.5 (CLC Bio, Aarhus, Denmark) for de novo assembly with a 500-bp minimum threshold resulting in 127 contigs. The draft genome consisted of 4,372,178 nucleotides and was annotated by rapid annotations using subsystems technology (RAST) (12). RAST annotation showed that Acinetobacter calcoaceticus PHEA-2 (score, 503) and Acinetobacter sp.…”
mentioning
confidence: 99%
“…The reads were de novo assembled using the hierarchical genome assembly process (HGAP) algorithm version 2 (Chin et al, 2013) to generate the complete genome of P. donghaensis JH1 T , which consists of 2 polished contigs with an average genome coverage of 145.5 fold. The genome was annotated using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP) version 2.10 (Tatusova et al, 2016), Rapid Annotation using Subsystem Technology (RAST) version 3.0 (Aziz et al, 2008;Overbeek et al, 2014) and IMG ER pipeline (Markowitz et al, 2009). The genome project and the complete genome sequence were deposited in the Genomes On Line Database (Liolios et al, 2010) and GenBank.…”
mentioning
confidence: 99%
“…Genome annotation was then performed using NCBI Prokaryotic Genome Annotation Pipeline (PGAP) version 2.10 and Rapid Annotation using Subsystem Technology (RAST) version 3.0 (Aziz et al, 2008, Overbeek et al, 2014, Brettin et al, 2015, Xia et al, 2015. The genome of Pseudomonas sp.…”
mentioning
confidence: 99%